Are Chinese workers from the one-child-policy generation selfish in a group? Evidence from worker surveys in six major Chinese cities - Yoshihiko Kadoya; Yoshio Sano (Osaka University, Institute of Social and Economic Research (ISER), 2014)
Many claim that Chinese people born after the one-child policy of 1979 are very individualistic or even selfish. This research tested the hypothesis that Chinese workers of the one-child-policy generation have difficulty working in a team, addressing the absence of nation-wide evidence. Using workers' surveys, for the first time, across six major Chinese cities, the results denied the hypothesis, at least in the workplace.
Keywords: J8; M20; R1; 330; one-child policy; chinese economy; labor farce quality; foreign direct investment